TEACHERS' CONTENT KNOWLEDGE AND ATTITUDE AS PREDICTORS OF STUDENTS' ACHIEVEMENT IN ENGLISH LANGUAGE IN SELECTED SENIOR SECONDARY SCHOOLS IN IBADAN METROPOLIS - NWENE, ENU; OLANIYI , AWOLERE (African Journal of Education and Practice, 2022)
Purpose: In spite of the fact that English language is very important in the society the performance of the students in the recent time in English language examination is not encouraging. Several factors have been mentioned as being responsible to students' inability to perform very well, such as teaching strategies and students' attitude. This study therefore examined teachers' content knowledge and attitude as predictors of students' achievement in English language in Ibadan Metropolis Methodology: Descriptive research design was adopted using forty-four (44) teachers and One thousand seven hundred and sixteen (1716) senior secondary two students selected through random sampling technique. Three research instruments were used to generate data namely: Teachers' attitude to English language teaching questionnaire, Teachers subject mastery scale and English language achievement test. The data collected were analysed using multiple regressive at 0.05 level of significance. Results: Findings indicated that there is a significant positive relationship between teachers' subject mastery and students' achievement (r=0.614; p<0.05). Also, there is significant positive correlation between Teachers attitude and students" achievement in English language (0.284; p<0.05). There is a composite relationship between the two independent variables and the dependent variable (academic achievement) (R =0.732). The independent variables accounted for 53.6% of the total variance in the students' academic achievement (Adjusted R2 =0.536) and this composite contribution is significant (F(2,1714) = 28.921; p>0.05. Subject mastery had significant relative contribution to achievement (Î² = 0.037; t=3.105, p<0.05) and teachers attitude also had significant relative contribution to achievement (Î²=0.102; t=4.087; p>0.05). Unique contribution to theory, practice and policy: It was recommended, therefore that teachers should have a good content knowledge to improve students' performance in English language and the government should make sure that teachers employed to teach at various levels of learning most possess the necessary content knowledge.